Balancing for an effective communication in organizations - Islam, A. S. M. Touhidul; Sorooshian, Shahryar (Springer Netherlands, 2018)
Communication is an essential part of all activities of organizations. However, it is affected by technology. Today, email and social media are popular methods of communication in organizations. Each of the listed methods has advantages and disadvantages which will be discussed in this letter which tries to drive the attention of organizations to the need for a standard and balanced approach toward communication.